2013
DOI: 10.1186/1824-7288-39-78
|View full text |Cite
|
Sign up to set email alerts
|

Childhood asthma and vitamin D deficiency in Turkey: is there cause and effect relationship between them?

Abstract: BackgroundEpidemiological studies show that vitamin D deficiency and insufficiency are common worldwide and associated with many diseases including asthma. Our aim was to evaluate vitamin D insufficiency and its clinical consequences.MethodsThis cross-sectional study was carried out on 170 children consisted of 85 who were asthmatic and 85 who were not, aged 2 to 14 years in Tekirdag, Turkey, from September 2009 to May 2010. Children’s basal serum D vitamin levels were determined, and their eating habits, vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 30 publications
4
50
1
5
Order By: Relevance
“…The mean duration of daily sunlight exposure between 10am and 3pm was 120.00± 5.11 minutes in children with asthma, which was significantly lesser than the 142.39±4.33 minutes in the healthy controls. This has been seen previously in a study done by Uysalol M et al, in Turkey [22]. The children with bronchial asthma having vitamin D deficiency(≤15ng/mL) in our study had a significantly lower FEV1% and FEV1/FVC% than bronchial asthma patients with insufficient vitamin D levels(>15ng/mL to <20ng/mL).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The mean duration of daily sunlight exposure between 10am and 3pm was 120.00± 5.11 minutes in children with asthma, which was significantly lesser than the 142.39±4.33 minutes in the healthy controls. This has been seen previously in a study done by Uysalol M et al, in Turkey [22]. The children with bronchial asthma having vitamin D deficiency(≤15ng/mL) in our study had a significantly lower FEV1% and FEV1/FVC% than bronchial asthma patients with insufficient vitamin D levels(>15ng/mL to <20ng/mL).…”
Section: Discussionsupporting
confidence: 74%
“…Vitamin-D deficiency has been linked to many disorders having an immunological basis like multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease, Crohn's disease, type 2 diabetes mellitus and cardiovascular disease [15,17,22]. Vitamin-D has been proposed to have modulatory actions on the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Başvuruda hasta ve kontrol grubundaki çocukların yaş, cinsiyet, boy, kilo, anne baba ve kardeşlerde allerjik hastalık varlığı (astım, allerjik rinit ve atopik dermatit), güneş ışığı maruziyeti süresi (saat 10 ile 15 arasında en az 10 dakika) kaydedildi (22).…”
Section: Gereç Ve Yöntemunclassified
“…Additionally, asthma severity is related to socioeconomic status and parental educa- 40 In a recent systematic review of cohort studies concerning the association between low vitamin D levels and asthma in children, 3 cohort studies were eligible: 2 studies reported positive association, and the third found no association. 41 The high prevalence of vitamin D deficiency (36.6%) and insufficiency (46.5%) in our group of children with asthma is in agreement with previous studies.…”
Section: F Enomentioning
confidence: 99%